2019
DOI: 10.1111/gcb.14775
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting frost‐induced tropical tree mortality patterns

Abstract: Extreme climatic and weather events are increasing in frequency and intensity across the world causing episodes of widespread tree mortality in many forested ecosystems. However, we have a limited understanding about which local factors influence tree mortality patterns, restricting our ability to predict tree mortality, especially within topographically complex tropical landscapes with a matrix of mature and secondary forests. We investigated the effects of two major local factors, topography and forest succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Jentsch et al () advocated for new generation of climate‐change experiments focused specifically on the study of climatic events, not trends. Since then, the number of studies focused on climatic events has continued to increase, with recent studies focused on heat waves (e.g., McKechnie & Wolf, ; Siegle, Taylor, & O'Connor, ), cold snaps (e.g, Bojorquez, Alvarez‐Yepiz, Burquez, & Martinez‐Yrizar, ; Leriorato & Nakamura, ), drought (e.g, Jentsch et al, ; Sankaran, ), flooding (e.g., Rivas, Spinola, Arrieta, & Faife‐Cabrera, ; Ujvari, Brown, Shine, & Madsen, ; Woodward, Bonada, Feeley, & Giller, ) and wildfire events (e.g., Cooper et al, ; Hale et al, ), among many others. However, while this emphasis has emerged recently in the context of climate change, these questions have deep roots in the study of event‐driven dynamics more generally.…”
Section: Toward a More Temporally Explicit Community Ecologymentioning
confidence: 99%
“…Jentsch et al () advocated for new generation of climate‐change experiments focused specifically on the study of climatic events, not trends. Since then, the number of studies focused on climatic events has continued to increase, with recent studies focused on heat waves (e.g., McKechnie & Wolf, ; Siegle, Taylor, & O'Connor, ), cold snaps (e.g, Bojorquez, Alvarez‐Yepiz, Burquez, & Martinez‐Yrizar, ; Leriorato & Nakamura, ), drought (e.g, Jentsch et al, ; Sankaran, ), flooding (e.g., Rivas, Spinola, Arrieta, & Faife‐Cabrera, ; Ujvari, Brown, Shine, & Madsen, ; Woodward, Bonada, Feeley, & Giller, ) and wildfire events (e.g., Cooper et al, ; Hale et al, ), among many others. However, while this emphasis has emerged recently in the context of climate change, these questions have deep roots in the study of event‐driven dynamics more generally.…”
Section: Toward a More Temporally Explicit Community Ecologymentioning
confidence: 99%
“…The most common type of damage was incline/bent trunks and broken branches and almost half of damaged individuals resprouted (Jimenez‐Rodríguez et al ). In comparison, the extreme frost in 2011 caused more than 90% of trees to die at severely affected sites in the Alamos forest, where only a few scattered trees resprouted (Bojórquez et al ). Most forests worldwide have an average background mortality of 5.5% (Zhang et al ), reinforcing the notion that effects of extreme events are highly context dependent.…”
Section: Restoration Of Tropical Dry Forests After Different Extreme mentioning
confidence: 99%
“…In the following section, I present two examples of well-studied lowland tropical dry forests (e.g. Alvarez-Yépiz et al 2008, 2018Bojórquez et al 2019), subjected to similar land-use change but exposed to different recent climatic disturbances, to demonstrate how we could capitalize on their responses to extreme events to facilitate their restoration.…”
Section: Responses Of Tropical Forests To Extreme Disturbance Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is important to note that these events of frost mortality are observed not only in temperate regions, but also in tropical forests. In a recent study, it was shown that a widespread mortality event in a tropical dry forest from Mexico was related to an unusual combination of duration, intensity, and timing of a frost event (Bojórquez, Álvarez‐Yépiz, Búrquez, & Martínez‐Yrízar, ). Similarly, dieback events related to frost injury were also reported for species from the Mediterranean region (Jalili et al, ; Matusick, Ruthrof, Brouwers, & Hardy, ).…”
Section: Main Drivers Of Forest Dieback Under a Scenario Of Climate Cmentioning
confidence: 99%